Perbandingan Kinerja Citra Watermarking dengan Menggunakan Metode Discrete Wavelet Transform (DWT) dan Discrete Cosinus Transform (DCT) - Baharuddin, Baharuddin (Lembaga Penelitian Universitas Negeri Padang, 2008)
The Research we propose is to compare watermarking method using Discrete Wavelet Transform (DWT) with Discrete Cosinus Transform (DCT). From these two methods, we will see the comparison of image has been given watermarking. By looking at the results of these two methods, the owner of digital image can select the best method to protect his data based to his need. Â The watermarked image will be analyzed objectively by means square error (MSE) and peak-to-peak signal to noise ratio (PSNR). Then we will look at its influences after given noise degradation. The simulation results showed the Discrete Wavelet Transform (DWT) methods is the best if it is compare to Discrete Cosinus Transform (DCT). Keywords: DWT, DCT, image processing, noise, MSE, PSNR